Effects of sexuality on frailty and quality of life in the elderly: a cross-sectional study - Edison Vitório de Souza Júnior; Cristiane dos Santos Silva; Uanderson Silva Pirôpo; Brenaráise Freitas Martins dos Santos; Tarcísio Pereira Guedes; Lais Reis Siqueira; Namie Okino Sawada
ABSTRACT Objectives: to analyze the effects of sexuality on frailty and quality of life in the elderly. Methods: a sectional study conducted with 662 elderly people between July and October 2020. Four self-administered instruments were used to collect bio-sociodemographic variables, sexuality, frailty and quality of life. Correlation analysis and structural equation modeling were performed. Results: among the dimensions that assess sexuality, sexual intercourse had a weak, positive effect on quality of life (SC: 0.134, 95%CI: 0.153 - 0.254, p = 0.027), while affective relationships had a strong, positive effect (SC: 0.556, 95%CI: 0.442 - 0.670, p < 0.001). Frailty was only significantly related to a weak to moderate negative effect with sexual intercourse (SC: -0.216, 95%CI: -0.385 - -0.047, p = 0.012). Conclusions: two dimensions of sexuality, Sexual intercourse and Affective relationships, were found to have an effect on the quality of life and frailty of the elderly people investigated.